2014
DOI: 10.5194/acp-14-12613-2014
|View full text |Cite
|
Sign up to set email alerts
|

Overview and sample applications of SMILES and Odin-SMR retrievals of upper tropospheric humidity and cloud ice mass

Abstract: Abstract. Retrievals of cloud ice mass and humidity from the Superconducting Submillimeter-Wave Limb-Emission Sounder (SMILES) and the Odin-SMR (Sub-Millimetre Radiometer) limb sounder are presented and example applications of the data are given. SMILES data give an unprecedented view of the diurnal variation of cloud ice mass. Mean regional diurnal cycles are reported and compared to some global climate models. Some improvements in the models regarding diurnal timing and relative amplitude were noted, but the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 43 publications
5
22
1
Order By: Relevance
“…Since Kottayil et al (2013) did not exclude the surface affected data, the results for the lower channels cannot be compared. Haffke and Magnusdottir (2015) reported a large inhomogeneity in the diurnal variation of precipitation which is consistent with the inhomogeneity we have found for relative humidity. Using Tropical Rainfall Measuring Mission (TRMM) Precipitation Radar measurements, Biasutti et al (2011) reported a large difference between diurnal variation of precipitation over coastal lands (early afternoon peak) and near shores (early morning) influenced by the land/sea breeze.…”
Section: Amplitude and Peak Timesupporting
confidence: 90%
“…Since Kottayil et al (2013) did not exclude the surface affected data, the results for the lower channels cannot be compared. Haffke and Magnusdottir (2015) reported a large inhomogeneity in the diurnal variation of precipitation which is consistent with the inhomogeneity we have found for relative humidity. Using Tropical Rainfall Measuring Mission (TRMM) Precipitation Radar measurements, Biasutti et al (2011) reported a large difference between diurnal variation of precipitation over coastal lands (early afternoon peak) and near shores (early morning) influenced by the land/sea breeze.…”
Section: Amplitude and Peak Timesupporting
confidence: 90%
“…ARTS is a freely available software package, which has been designed for radiative transfer simulations for the mm and sub-mm spectral range, including polarization capabilities. ARTS has been comprehensively tested by comparison to a range of other MW radiative transfer models [59,60] and its performance has been demonstrated in various applications [11,12,14,44]. It can be operated in spherical geometry for 1D, 2D, and 3D atmospheres, and thus, it can be employed for a wide range of remote sensing applications.…”
Section: Atmospheric Radiative Transfer Simulatormentioning
confidence: 99%
“…Toward that end, the upcoming Ice Cloud Imager (ICI) instrument, which covers frequencies between 183.31 GHz and 668 GHz, on board the Meteorological Operational Satellite-Second Generation (Metop-SG) [9] operated by the European Organization of Meteorological Satellites (EUMETSAT), is going to fill this gap [10]. The performance of the sub-mm wavelengths in terms of retrieving ice properties has been manifested by airborne and limb sounding instruments; e.g., the International Submillimetre Airborne Radiometer (ISMAR) [11,12], the Compact Scanning Submillimeter-wave Imaging Radiometer (CoSSIR) [13], Superconducting Submillimeter-Wave Limb-Emission Sounder (SMILES), and the Odin-Sub-Millimetre Radiometer (Odin-SMR) [14]. Accordingly, ICI, with frequencies sensitive to the size, content, shape, and orientation of ice hydrometeors, aims at improving the representation of ice-containing clouds in NWP models.…”
mentioning
confidence: 99%
“…The suitability of the submillimeter region for ice cloud retrievals has already been demonstrated using limb sounding instruments mainly devoted to stratospheric chemistry. Specifically, the Microwave Limb Sounder (MLS) (Waters et al 2006) with channels at 240 and 640 GHz and the submillimeter radiometer (SMR) on board the Odin satellite (Murtagh et al 2002) with channels between 500 and 650 GHz provide information on upper-tropospheric ice water content (Wu et al 2008, Eriksson et al 2014. The gap in terms of global ice cloud and light snow climatologies will be closed by the Ice Cloud Imager (ICI) on MetOP-SG to be launched 2021 (Bergada et al 2016).…”
Section: Microwave Radiometers For Measurement Of Atmospheric Ice mentioning
confidence: 99%